Формулы произведения тригонометрических функций
$$sin\alpha \cdot sin\beta = \frac{cos(\alpha - \beta)-cos(\alpha + \beta)}{2}$$
$$sin\alpha \cdot cos\beta = \frac{sin(\alpha - \beta)+sin(\alpha + \beta)}{2}$$
$$cos\alpha \cdot cos\beta = \frac{cos(\alpha - \beta)+cos(\alpha + \beta)}{2}$$
\begin{align} tg\alpha \cdot tg\beta & = \frac{cos(\alpha - \beta)-cos(\alpha + \beta)}{cos(\alpha - \beta)+cos(\alpha + \beta)}\\ &= \frac{tg\alpha + tg\beta}{ctg\alpha + ctg\beta} \end{align}
\begin{align} ctg\alpha \cdot ctg\beta & = \frac{cos(\alpha - \beta)+cos(\alpha + \beta)}{cos(\alpha - \beta)-cos(\alpha + \beta)}\\ &= \frac{ctg\alpha + ctg\beta}{tg\alpha + tg\beta} \end{align}
$$tg\alpha \cdot ctg\beta = \frac{sin(\alpha - \beta)+sin(\alpha + \beta)}{sin(\alpha + \beta)-sin(\alpha - \beta)}$$
comments powered by HyperComments
© 2012–2019 100Формул.ru
Написать нам: info@100formul.ru
Яндекс.Метрика